KAJIAN KEANEKARAGAMAN FLORA & FAUNA DI NEGERI TITAWAAI PULAU NUSALAUT, KABUPATEN MALUKU TENGAH Research on the Flora and Fauna Diversity in Titawaai Village, Nusalaut Island, Central Maluku Regency - Henderina Lelloltery; Andry Tuhumury; Edward Ridolf Kesaulya; Fransina Sarah Latumahina; Herman Siruru; Sofia Mustamu (Lambung Mangkurat University-Indonesia, 2026)
This research aims to determine the level of flora and fauna diversity in Titawaai Village. Data collection focused on plant species diversity using the quadrat strip method and on wildlife observation using the variable circular-plot method. Wildlife observation during the research period included both direct and indirect sightings (sounds, tracks, droppings, nests, feeding remains, scratch marks, and/or other indications). The floral and faunal potential in Titawaai Village includes 15 species of birds and 1 species of mammal, with a conservation status comprising 5 endemic animal species. This potential is supported by habitat conditions in the form of vegetation which serves as a food source, seed disperser, and canopy layer that plays a role in maintaining microclimate stability and providing energy resources. The diverse vegetation composition consists of : 21 species at the tree level, dominated by several local species such as clove (Syzygium aromaticum (L.)); 17 species at the pole level, dominated by kayu kinar (Mallotus japonicus); 15 species at the sapling level, dominated by red gohi (Ficus melinocarpa Blume); and 7 species at the seedling level, dominated by kayu raja (Endospermum moluccanum).